2007
DOI: 10.1002/anie.200703437
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Catalysis for a One‐Pot Regioselective Protection of Carbohydrates: The Example of Glucose

Abstract: Fine‐tuning the conditions for a tandem reaction using a single catalyst in a single reaction vessel leads to carbohydrate building blocks displaying different patterns of protecting groups (see picture). This process greatly simplifies the access to oligomers, as illustrated by the rapid assembly of a trisaccharide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 58 publications
1
65
0
Order By: Relevance
“…Compound 1 was obtained after a Swern oxidation of methyl 3-Obenzyl-4,6-O-benzylidene-a-D-glucopyranoside. 9 The crude 2-ulose 1 was submitted to acetone and L-proline (30 mol %) in DMSO and led exclusively to aldol 2 in 97% yield over two steps. Similarly, starting from known ulose 3, 10 the aldol 4 was obtained in 65% yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 1 was obtained after a Swern oxidation of methyl 3-Obenzyl-4,6-O-benzylidene-a-D-glucopyranoside. 9 The crude 2-ulose 1 was submitted to acetone and L-proline (30 mol %) in DMSO and led exclusively to aldol 2 in 97% yield over two steps. Similarly, starting from known ulose 3, 10 the aldol 4 was obtained in 65% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Hz, H-1 0 ), 5.70 (d, 1H, J 5,6 ¼8.1 Hz, H-6), 4.31 (d, 1H, J 1 0 ,2 0 ¼0 9. Hz, H-2 0 ), 4.10 (dd, 1H, J 4 0 ,5 0 a ¼5.1 Hz, J 5 0 a 0 ,5 0 b ¼10.2 Hz, H-5 0 a), 3.98 (m, 2H, H-4 0 , H-5 0 b), 3.34 (s, 3H, NCH 3 ), 2.99 (d, 1H, J A,B ¼18 Hz, H-A (CH 2 CO)), 2.89 (d, 1H, J A,B ¼18 Hz, H-B (CH 2 CO)), 2.19 (s, 3H, CH 3 ), 0.89, 0.86 (s, 18H, 2Â t-Bu), 0.23, 0.15, 0.13, 0.08 (s, 12H, 4Â SiCH 3 ); 13 C NMR (CDCl 3 , 75 MHz): d 209.1 (CO), 163.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Convergent synthetic strategies that allow the convenient assembly of complex oligosaccharides from properly protected building units involving a minimum number of synthetic steps have become available. In particular, one-pot multi-step approaches for selective monosaccharide protection45, 46 and oligosaccharide assembly are being pursued, which do not require intermediate work-up and purification steps and hence speed-up the process of chemical synthesis considerably. Several research groups have demonstrated that chemoselective, orthogonal and iterative glycosylation strategies, which exploit differential reactivities of anomeric leaving groups, allow several selected glycosyl donors to react in a specific order resulting in a single oligosaccharide product 4749, 98100.…”
Section: The Classical Approach For Carbohydrate-based Vaccine Devmentioning
confidence: 99%
“…7 A three-step procedure for the conversion of 6 to iodide 7 began with AcOH-mediated hydrolysis of the benzylidene acetal, followed by selective Wittig iodination of the resultant primary hydroxyl group and TBS protection of the remaining secondary carbinol in 90% overall yield. Sonication of 7 with activated zinc powder promoted reductive fragmentation to generate an aldehyde intermediate, 8 which upon treatment with an organocerium reagent derived from vinylmagnesium bromide furnished allylic alcohol 8 as an inconsequential diastereomeric mixture in 75% yield over two steps.…”
mentioning
confidence: 99%